Properties and Applications of Biomaterials Related to Gels - Wang, Shige (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This reprint consists of 12 papers, of which 2 are editorials and 10 are research papers. We hope to share the experimental and research results in this field and inspire new ideas for the design and applications of hydrogels.